PEMURNIAN ANETOL DARI MINYAK ADAS (FOENICULUM VULGARE MILL) DENGAN DISTILASI FRAKSINASI PENGURANGAN TEKANAN - Suciati, Dwimaryam (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2017)
Anethole is an essensial oil that isolated from the fruit of aniseed (Foeniculum vulgare Mill) which be used as raw material in synthesis of some medicine. Their biological activities as well as  the flavoring properties are due to the anethole compound. The quality of this essential oils are based how much anethole they has. Separation and purification of anethole components on it have been performed by using themethod of fractionation distillation under reducedpressure. Fractionationdistillation under reduced pressure was done with 3 mmHg pressure and variation of reflux time of distillation. Anethole as colorless liquid with strong odor was obtained in second fractions of distillate in 77% yield with96% purity.The identification of the products were carried out bymeans of gas chromatography (GC), GC-MS, 1H-NMR spectrometers and FT-IRspectrophotometer.